The Most Memorable Moments in Olympic Swimming - Lohn, John (Rowman & Littlefield Publishers, 2014)
Every four years the summer Olympic Games capture the world’s attention. Over 10,000 athletes from more than 200 countries gather to prove they are the best in their sports. From the first competition held in 1896 to the 2012 London Olympics, the games have hosted some of swimming’s greatest victories and toughest defeats. Fans have witnessed Johnny Weissmuller win back-to-back Olympic gold medals before he found fame on the big screen as Tarzan; they have seen Dara Torres defy age to win three silver medals at the age of 41; and they will forever remember Michael Phelps capturing a record eight gold medals at the 2008 games. The Most Memorable Moments in Olympic Swimming relives the sport’s greatest moments on its biggest stage. Through careful research and the personal recollections from the athletes themselves, John Lohn has brought together the key performances, top athletes, major controversies, and improbable victories of the games. Organized chronologically, the progression of swimming as an Olympic sport comes to life as the top 25 moments are revealed. The best swimmers in Olympic history are featured throughout, from Mark Spitz and Ian Thorpe to Debbie Meyer and Dawn Fraser. Dozens of photographs highlight the athletes and their shared passion for swimming glory. Detailed appendixes include the top Olympic medal winners by country and by athlete, and a bibliography provides key swimming references for the reader. Swimming fans, coaches, athletes, and researchers will enjoy this history of a sport rich in tradition and spectacular moments.